2004
DOI: 10.1128/iai.72.3.1603-1607.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies That Inhibit Binding of Plasmodium falciparum -Infected Erythrocytes to Chondroitin Sulfate A and to the C Terminus of Merozoite Surface Protein 1 Correlate with Reduced Placental Malaria in Cameroonian Women

Abstract: Plasmodium falciparum-infected erythrocytes often sequester in the placenta of pregnant women, producing placental malaria, a condition that can compromise the health of the developing fetus. Scientists are hopeful that a vaccine can be developed to prevent this condition. Immunological mechanisms responsible for eliminating parasites from the placenta remain unclear, but antibodies to the carboxyl-terminal 19-kDa segment of the merozoite surface protein 1 (MSP1-19), the ring-infected erythrocyte surface antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 23 publications
3
29
0
2
Order By: Relevance
“…This corresponds well with the finding that VSA PAM -specific IgG responses appear around weeks 18 to 20 in primigravidae and somewhat earlier in multigravidae (22,30). The weak, but highly significant, negative association between VSA PAM -specific IgG3 and gestational age that we found in samples from Yaounde may thus reflect catabolic antibody decay toward the end of pregnancy following VSA PAM -specific antibody-mediated control of placental parasite multiplication (11,(30)(31)(32). The fact that this was not seen for IgG1 was probably related to the longer half-life of this subclass, and the fact that it was not seen in the samples from Etoa may be related to the higher endemicity, less drug usage (Table 1), and/or inadequate sample size.…”
Section: Discussionsupporting
confidence: 76%
“…This corresponds well with the finding that VSA PAM -specific IgG responses appear around weeks 18 to 20 in primigravidae and somewhat earlier in multigravidae (22,30). The weak, but highly significant, negative association between VSA PAM -specific IgG3 and gestational age that we found in samples from Yaounde may thus reflect catabolic antibody decay toward the end of pregnancy following VSA PAM -specific antibody-mediated control of placental parasite multiplication (11,(30)(31)(32). The fact that this was not seen for IgG1 was probably related to the longer half-life of this subclass, and the fact that it was not seen in the samples from Etoa may be related to the higher endemicity, less drug usage (Table 1), and/or inadequate sample size.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of IRBCs frequently induces the infiltration of inflammatory-type cells into the placenta, where they cause pathological alterations (26). It has been also shown that P. falciparum trophozoite infected human red cells produce H 2 O 2 and OH ¯ radical about twice as much as normal erythrocytes (17,27).…”
Section: Discussionmentioning
confidence: 99%
“…Titers of RESA-specific antibodies were lower in pregnant than non-pregnant women in some studies [129], but not others [52, 64], or were lower in primigravid than multigravid women in some studies [52,129], but not others [2,51]. Anti-RESA antibody levels by immunofluorescence or ELISA were inversely associated with parasitemia in some studies [8,129], but not others [52,184]. Higher levels of antibodies to merozoite surface protein 1 have also been associated with reduced risk of placental malaria in some studies [27,184] but not in others [76,126].…”
Section: Antibodies To Other Antigensmentioning
confidence: 96%